Regional cancer burdens: a retrospective analysis of demographic and diagnostic patterns in Bangladesh - Kundu, Samiran; Chakrabarty, Sandipan; Chakrabortty, Phalguni; Nirob, Mohibur Hossain; Monjur-E-Elahi, M. (International Journal of Research in Medical Sciences, 2025)
Background: Regional cancer data from low and middle-income countries (LMICs) like Bangladesh remain limited, hindering evidence-based oncology planning. This study examines demographic and diagnostic patterns among cancer patients at two tertiary centers in northern Bangladesh to inform resource-sensitive cancer control strategies. Methods: We conducted a retrospective analysis of 547 cancer cases diagnosed between 2019 and 2021 at two major tertiary care centers. Patient records were reviewed for age, sex, residential location and cancer type. Descriptive statistics were applied to explore demographic distributions and diagnostic trends over time. Results: The 41–60 years age group consistently accounted for the majority of cases, followed by the 61–80 years group. Females represented a growing proportion of diagnoses, increasing from 60.64% in 2019 to 69.92% in 2021. Breast cancer was the most prevalent malignancy each year (37.35% in 2019; 45.71% in 2020; 42.28% in 2021). Colorectal, stomach, cervical and lung cancers followed in frequency, with lung cancer showing an upward trend in 2021 (12.20%). Geographic analysis showed the largest patient share from Sadar, with consistent contributions from Birgonj, Birol and Phulbari and steady representation from peripheral areas over the three years. Conclusions: This study reveals stable demographic patterns and evolving cancer type distributions in a regional Bangladeshi population. The increasing female predominance and persistent burden of breast cancer highlight the need for gender-sensitive screening programs. The rising proportion of lung cancer and continued diagnostic insufficiency underscore the importance of strengthening cancer registries, decentralizing oncology services and improving access to care in remote areas of LMICs.